All-on-4 implant treatment: common difficulties and methods for coping: Konsep All-on-4 dalam kedokteran gigi implan: kesulitan umum dan solusinya - Nur Inriany; Eri Hendra Jubhari (Makassar Dental Journal, 2021)
The All-on-4® concept is one of the treatment procedures used in total edentulous patients and as an alternative to the routine care of conventional dentures with successful results in short term, long term and retrospective studies. What needs to be con-sidered in alternative treatments lies in the success of the prosthesis and its prosthodontic perspective which involves the princi-ples of occlusion. This article reviews the All-on-4® concept and its prosthodontic aspects. All-on-4® style dental implant treat-ment is a multi-step process with many potential complications. Reports of success rates for dental implants and final prosthe-ses have been widely published while the dental literature on the barriers and difficulties associated with the treatment of dental implants with the All-on-4 concept has not been widely reported. In the current article, the author describes common problems before, during, and after All-on-4 style dental implant treatment of more than 500 arches and discusses methods for overcoming those barriers.